KRISIS PERADABAN SEBAGAI KRISIS AKAL BUDI: Dialog dengan Pemikiran Edmund Husserl di dalam Die Krisis der europäischen Wissenschaft und die transzendentale Phänomenologie, eine Einleitung in die phänomenologische Philosophie - Reza A.A Wattimena (Litbang STFT Widya Sasana Malang, 2016)
Husserl wrote a book Die Krisis der europäischen Wissenschaft und die transzendentale Phänomenologie, eine Einleitung in die phänomenologische Philosophie as an effort to understand the situations in Europe at the begining of 20th century. He saw that Europe experienced crisis of cilivation that has root in the crisis of reason itself. Husserl tried to analyze the root of this crisis and provided possible solutions in the form of transcendental phenomenology. One of the most important concept in the transcendental phenomenology is the concept of lifeworld.Hussserl’s arguments are still relevant to understand our current situations in the begining of 21th century. However, several assumptions of his arguments have to be read critically